PENGARUH PENAMBAHAN VITAMIN E PADA RANSUM TERHADAP FERTILITAS PUYUH - Endah Subekti (MEDIAGRO, 2012)
This study aims to determine the effect of vitamin E in the diet on fertility of quail eggs. The material used in this study were male quail aged 60 days at 60 head, and quail females age 35 days 180 tails. Basic rations used is non-commercial rations prepared with crude protein content of 22.5 % and 2600 kcal.kg metabolizable energy ( E ). Ration treatment by adding a basic ration plus vitamin E 30 IU / kg ( E1 ), the basic ration plus vitamin E 40 IU / kg ( E2 ) and a base diet plus vitamin E 50 IU / kg ( E3 ). Rations and drinking water given adlibitum. Data taken include feed intake, egg production, egg weight, egg vitamin E and fertility. The data captured is analyzed using a variance Complete Design Patterns. Unidirectional and if there is a significant contrast between the test continued treatment . The results showed that the addition of vitamin E in the diet does not provide a significant difference on feed intake, egg production, egg weight and the effect but a significant increase ( P < 0.01 ) the increase in the amount of vitamin E in eggs and egg fertility enhancement. Keywords : Quail, Vitamin E, Fertility